Rising Popularity of Internet Memes in India: A Media Psychology Perspective - Dr. Shiv Shankar Das, (Indian Journal of Social Science and Literature (IJSSL), 2024)
The psychology behind internet memes is complex and multi-faceted, drawing on various aspects of human behaviour and cognitive processes. Memes have become a part of the social media culture and its popularity continues to grow in India. The analysis of internet memes can provide valuable insights into the cultural, social, and psychological aspects of our online lives. In the field of media psychology, the impact of memes on human behaviour and cognition is a growing area of research. Researchers are exploring the ways in which memes can be used to shape social attitudes, as well as the psychological mechanisms behind their popularity and spread. Media psychology and memes are both important areas of study that shed light on the ways in which communication occurs in contemporary society. By examining the relationship between media messages and the psychological processes that underlie them, we can gain a better understanding of how communication shapes our attitudes, beliefs, and behaviours. In the context of memes, the emotions evoked by a meme can be amplified through its spread and can have a significant impact on public opinion and discourse. Based on qualitative analysis, the paper employs the Social Cognitive Theory along with Uses and Gratifications Theory to decode the manifestation of memes in our social system and creation of echo chambers.